2014
DOI: 10.1007/s40333-014-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential habitat modeling for reintroduction of three native plant species in central Iran

Abstract: Potential habitat modeling of endemic species is an appropriate method to maintain biodiversity, ecosystem function and rehabilitation of rangeland ecosystems. Astragalus caragana, A. cyclophyllon and A. podolobus are endemic in Iran's rangelands and some neighboring countries. The three native species could endure environmental stresses due to their distinctive ecophysiological characteristics. They play important roles in sustainable pastures production, recreation and improvement. They suffer severe threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…The results showed that the predicted suitable habitats through MaxEnt almost always appeared as over predicted in some areas compared to the realized niche of the species. Because, MaxEnt considers only nichebased presence data, it estimates the species fundamental niche (different from occupied niche) rather than realized niche (Kumar and Stohlgren, 2009;Yang et al, 2013;Ardestani et al, 2015). The overall study provides perfect baseline information for planning conservation and management strategies to protect such unique medicinally important plant species of Himalaya.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the predicted suitable habitats through MaxEnt almost always appeared as over predicted in some areas compared to the realized niche of the species. Because, MaxEnt considers only nichebased presence data, it estimates the species fundamental niche (different from occupied niche) rather than realized niche (Kumar and Stohlgren, 2009;Yang et al, 2013;Ardestani et al, 2015). The overall study provides perfect baseline information for planning conservation and management strategies to protect such unique medicinally important plant species of Himalaya.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated biological tolerances and habitat preferences for both Cola lorougnonis and Drypetes singroboensis species (Ardestani et al, 2015). The application of a jackknife evaluation procedure allowed the confirmation of the importance of these variables.…”
Section: Climatic Variable Ranges For the Distribution Of Cola Lorougmentioning
confidence: 67%
“…In contrary, the eleven species with AUC ranging from 0.9 and 0.99 are very restricted to climatic variables (Ardestani et al, 2015) Vol. 6, No.…”
Section: Suitable Habitats Comparison Between These Twenty One Rare Smentioning
confidence: 91%
“…Anyhow, as most of the threats are anthropogenic, in order of achieving more sustainable solutions, a systematic and interdisciplinary approach on biodiversity conservation has been required (Delanoë et al 1996, Tisdell 2014. For all of the sixteen taxa that have been studied and analysed, and in particular for the twelve of them that are critically endangered (CR), ex situ and in situ conservation programmes need to be combined appropriately and also the reintroduction of the projects is highly recommended (Ardestani et al 2015, Volis 2016.…”
Section: Discussionmentioning
confidence: 99%